Production protocol for organic tomato : (lycopersicon esculentum mill.). - Abijith Kumar V P (Department of Agronomy, College of Agriculture, 2011)
The research project entitled ‘Production protocol for organic tomato (Lycopersicon esculentum Mill.)’ was conducted at the Instructional Farm attached to the College of Agriculture, Vellayani during the year 2009-2010 to study the effects of organic nutrition and spacing and their interaction upon growth, yield, quality and nutrient uptake of tomato and to assess the residual effect of organic nutrition on the succeeding crop. The experiment was laid out in factorial randomized block design (RBD) with three replications. The treatments consisted of four levels of nutrients, N1 (full nitrogen substitution as organic), N2 (75% nitrogen only and as organic), N3 (50% nitrogen only and as organic) and N4 (Package of Practices Recommendations ‘Crops’: 2007 of Kerala Agricultural University) and three spacing viz., S1 (60 cm x 60 cm), S2 (60 cm x 45 cm) and S3 (60 cm x 30 cm). Before transplanting, the seedlings were given a root dip in Pseudomonas flourescens culture against bacterial wilt disease. The experiment was laid out as 4 x 3 factorial randomized block design (FRBD) with 3 replications. The number of treatments were 12 replication-1. Common treatments such as neem seed oil-garlic emulsion spray, pseudomonas spraying, trichoderma incorporation in the soil and uniform mulching at different intervals were also undertaken. From the results it was found that integrated supply of nutrients through FYM and chemical fertilizers gave the highest fruit yield in tomato. Among the different spacing, the widest spacing of 60 cm x 60 cm recorded the highest fruit yield plant-1. The interaction effects were significant with the highest yield in the combination where the individual effects of nutrient levels as well as spacing were significantly the highest, viz., N4S1. The fruit weight was also the highest in the same treatments and the crop duration the modest. The lowest fruit weight and the shortest duration of crop was observed in N3. The widest spaced plants produced the highest fruit weight and the combination involving POP recommendation and the widest spacing (N4S1) again produced the heaviest fruits. The fruit quality and appearance was also found the best in N1 and N4 when compared to other two levels. Spacing had no effect on the quality characters while the interaction between nutrient levels and spacing had significant effect on lycopene and TSS content with N1S1 giving the highest values for them. The dry weight of plants was found the highest in N1 and in the widest spacing (S1) and among the interaction the same combination produced the highest plant dry weight (N1S1). The nutrient uptake especially N and P was found the highest in N4 and K in N1. In closer planting the nutrient uptake was the highest consequent to the increase in population. The organic carbon and available nutrient status after the experiment was the highest in N1. The effect of nutrient levels and spacing were significant in benefit-cost ratio at the normal market price as well as the premium prices of the produce. The POP recommendation (N4) with an integrated nutrient approach with organic and inorganic sources fetched the highest B:C ratio. Similarly for planting distances, it was found that tomato cultivation become remunerative in terms of B:C ratio only when the plants were spaced at a closer distance than wider spacing. Inorder to study the residual effect of organic nutrition, a crop of amaranthus (Amaranthus tricolor) was raised after tomato and the biometric characters of the residual crop studied were influenced by nutrient levels with the highest values in N4 (control) and the lowest in N3. The marketable yield of amaranthus was also found the highest in N4 (control). Similarly the economics of amaranthus cultivation revealed the significance of N4 and S3 in producing the highest B:C ratio. The combination of N4 and S3 also recorded the highest B:C ratio in amaranthus. The uptake of nutrients especially N and K was found the highest in N4 and N1. Though spacing had no significant role in the uptake of nutrients, the combination of nutrient levels and spacing had significant influence and the highest uptake was observed in N4S3. The combined B:C ratio of tomato-amaranthus sequence was determined at the premium price of tomato plus the market price of amaranthus by assuming a 20 % hike for the organic produce in the market. The effect of nutrient levels and spacing were significant with N4 giving the highest B:C ratio and N3 the lowest. The closely spaced plants (S3) recorded the highest B:C ratio and the widest spaced plants (S1), the lowest. The interaction effect was significant with the highest B:C ratio in N4S3 and the lowest in N3S1. Among the organic treatments N1 was found the best with a combined B:C ratio of 1.38 followed by N2 (1.00) and the lowest in N3 (0.78). Among the organic combination with spacing it was in N1S3 the highest B:C ratio found (1.42) followed by N1S2 (1.36) and N1S1 (1.35).